Application of the Fuzzy VIKOR Method for Decision-Making in Bamboo Product Development - Thongkaew, Somsak; Hongthong, Sakchai; nasawat, pariwat; Kanchanaruangrong, Nattapat; Taptimdee, Weerapol; Chongsri, Krisana (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
This research presents the application of the Fuzzy VIKOR method as a multi-criteria decision-making (MCDM) technique to determine the most suitable approach for developing bamboo-based products. The study began by defining five decision criteria: production cost (C1) marketing (C2) government support research and innovation (C3) collaboration between communities and entrepreneurs (C4) and environmental sustainability (C5). Eight alternatives were considered, including household products (A1), furniture and decorative items (A2), tools and equipment (A3) handicrafts and souvenirs (A4) eco-friendly products (A5) construction products (A6) health and beauty products (A7) and food and beverage products (A8). The evaluation was based on input from five experts. The results revealed that Alternative (A5) was the best option, with Si = 0.00, Ri = 0.00, Qi = 0.00, indicating the closest proximity to the ideal solution. Alternative (A8) had values of Si = 0.97, Ri =1.34, Qi = 0.36, while Alternative (A7) had values of Si = 0.81, Ri = 1.66, Qi = 0.45, respectively. The least suitable alternative was Alternative A6 had values of Si = 0.97, Ri = 3.79, Qi = 1.00 the highest values observed. This research demonstrates its effective application in decision-making when selecting complex approaches to bamboo product development.